Analisis Aspek Ergonomi Pada Proses Penggilingan Kedelai Pada Umkm Tahu Marina - Edi Patrisyus Barus; Sri Zetli (LPPM Universitas Putera Batam, 2019)
The aspect of ergonomics is greatly influenced by work attitude and work risk level.. Attention to the problem of ergonomics of workers is very less, especially in Micro Small Medium Enterprises (UMKM). UMKM Tahu Marina is one of the business ofmaking tofu in batam which has 6 employees. Based on observations in the field known in the process of soybean milling there is a problem of fatigue factor aspect of ergonomics. Therefore, in this research, ergonomic aspect analysis is done on knowingmilling process using REBA method through anthropometric measurement. This research is expected to analyze the fatigue level of the employees at UMKM Tahu Marina. Based on anthropometric measurement, it is known that the future range of theanthropometry in accordance with the anthropometry of the employee is 60.8 cm, the height of the vertical range of 135.3 cm and the height of the water tanks is 161.8 cm, whereas based on the final REBA score there is on the activity of raising soybean from floor to machine with Score 11. The lowest ergonomic level with a final REBA score of 9 is in the activity of taking soybeans.